(untitled) (El-Wahat Journal for Research and Studies, 2026)
The field of Islamic studies aims at the conception of working scholars, influential thinkers, ambitious reformers, and great leaders. These outputs are not attainable without a cross-disciplinary approach within the sharī’ah sphere on the one hand, and between sharī’ah and the fields of study needed by its specialist, on the other hand, for a better understanding of the complexity of reality in the aim of a successful guidance of it. That being said, this article tries to answer the following question: How important is the cross-disciplinary approach in the sharī’ah field? What is the reality of this complementarity? What are its manifestations and effects? The aim of the article is to investigate the concept of cross-disciplinary approach, its importance and its roots back to the dawn of the Islamic era. Also, it aims at discussing the reality of such complementarity and its implications for the sharī’ah field and its specialists as well.